Antibody response to BNT162b2 SARS-CoV-2 mRNA vaccine is not influenced by AB0 blood group in subjects with transfusion-dependent thalassemia: Serological response to COVID-19 vaccine among blood groups in TDT patients - SGHERZA, NICOLA; Zucano, Stefania; Vitucci, Angelantonio; Palma, Antonio; Campanale, Daniela; Larocca, Angela Maria Vittoria; Visceglie, Domenico; Acquafredda, Amalia; Musto, Pellegrino (Acta Biomedica Atenei Parmensis, 2022)
Not applicable